Cytoglobin Attenuates Neuroinflammation in Lipopolysaccharide-Activated Primary Preoptic Area Cells via NF-κB Pathway Inhibition - Gomes, Bruna R. B.; de Sousa, Gabriela Luna S.; Ott, Daniela; Murgott, Jolanta; de Sousa, Marcelo V.; de Souza, Paulo E. N.; Roth, Joachim; Veiga-Souza, Fabiane H. (Frontiers in Molecular Neuroscience, 2019)
Cytoglobin (Cygb) is a hexacoordinate protein, associated with the transport of oxygen, nitric oxide scavenging, tumor suppression and protection against oxidative stress and inflammation. This protein is expressed in brain areas including the preoptic area (POA) of the anterior hypothalamus, the region responsible for the regulation of body temperature. In this study, we show that Cygb is upregulated in the rat hypothalamus 2.5 h and 5 h after intravenous administration of lipopolysaccharide (LPS). We investigated the effect of treatment with Cygb in POA primary cultures stimulated with LPS for 4 h. The levels of tumor necrosis factor alpha (TNFα) and interleukin-6 (IL-6) were measured and the results showed that Cygb reduced the concentrations of both cytokines. We further observed a decrease in immunoreactivity of the inflammatory transcription factor NFκB, but not NF-IL6 and STAT3, in the nucleus of Cygb-treated POA cells. These findings suggest that Cygb attenuates the secretion of IL-6 and TNFα in LPS-stimulated POA primary cultures via inhibition of NFκB signaling pathway, indicating that this protein might play an important role in the control of neuroinflammation and fever.